Development of Real-Time Virtual Environment with Hierarchical Construction - Sulaiman, Hamzah Asyrani (2012)
The development of real-time virtual environment is always a fundamental task for research to come out with a good testing procedure. Regardless any software application that has been used to develop the virtual environment, maintaining real-time aspect such as physic simulation, fluid simulation, collision detection, and others is definitely important. Numerous attempts has been introduced in order to develop nearly perfect virtual environment but at the end the solution only cater for some specific settings that must be implemented before we properly visualize the virtual environment. In this paper, we consider few elements that can be used to visualize their virtual environment and perhaps becoming a common visualization procedure to differentiate and compare with others.